An Effort To Improve Reading Skills Through Picture Card Game Media For Grade 1 Students Of Elementary School 5 Banyumanis - Saadah, Mu’linatus (Universitas Sebelas Maret, 2022)
The role of the first grade teacher plays an important role in the field of teaching Indonesian, especially reading. Without having adequate reading skills from an early age, children will experience learning difficulties in the future. The ability to read is the main basis not only for the teaching of Indonesian language itself, but also for the teaching of other subjects. Teachers do not know the students thoroughly so that they cannot distinguish between students who are weak and students who are good at receiving learning. This research aims to (1) describe how flashcard games are used in grade 1 students at SD Negeri 5 Banyumanis, Donorojo Distrct, Academic Year 2022/2023 and to improve the reading ability of Beginning Indonesian for Grade 1 elementary school students.This research is classroom Action Research (PTK) carried out in 2 cycles with 3 meetings per cycle with a total of 8 students. In pre-action, the percentage of student completion only reached 23%, after the action was implemented in cycle I, the percentage of student completion increased to 55%, in cycle II it increased to 77% so the researcher did not continue to cycle III.